Knowledge management in tourism policy and governance applications - Fayos-sola, Eduardo; Jafari, Jafar; De Silva, Joao Albino Matos (Bridging tourism theory and practice, 2012)
Sixty years after its birth, contemporary tourism is at crossroads. It has grown to become a key element of economic well-being, but it is threatened and threatening. Its enemies are congestion, destruction of natural and cultural environments, and social unrest. However, it also contributes its fair share to these evils. How can tourism really become a fulcrum for development and sustainability in the 21st century? This is a matter of crucial importance for entrepreneurs, governments, and civil society stakeholders, and Knowledge Management in Tourism: Policy and Governance Applications provides these key players with answers and queries, and above all with the strategic tools to understand and act. Knowledge Management in Tourism: Policy and Governance Applications is an indispensable instrument for everyone interested in the theory and practice of this very important human pursuit: the quest for effectiveness, efficiency, and equity of tourism activities in helping build the future of mankind.